HUKUM PENODAAN AGAMA PERSPEKTIF FIKIH, PERUNDANG-UNDANGAN INDONESIA, DAN HUKUM INTERNASIONAL - Gusriawan Sholehudin Wahid; Muhammad Murtadha Asyrafi; Ismail Ismail; Achmad Abdi Ilhami; Muhammad Torieq Abdillah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This research aims to determine the views of Islamic jurisprudence, Indonesian legislation, and international law regarding religious blasphemy law. This research is normative legal research with a comparative and statutory approach. The results of this research show that there are differences in sanctions for blasphemy between Islamic jurisprudence, Indonesian legislation and international law. Fiqh views that the law on blasphemy can lead someone to become an apostate because it endangers the religion and its followers. Indonesian legislation views the law on religious blasphemy depending on the existing offense with legal consequences, such as the death penalty, imprisonment, imprisonment, fines, imprisonment, and even the revocation of certain rights. In international law, such as in Israel and Malaysia, punishment is given in the form of imprisonment or a fine for blasphemy of any religion, in contrast to Pakistan which applies the death penalty for blasphemy against Islam